(NsOWREMENNYJ RUSSKIJ QZYK (B:s (NtEORETI^ESKIJ KURS (B: (NsLOWOOBRAZOWANIE(B. (NmORFOLOGIQ (B: (Nu^EBNOE POSOBIE (B/s - (NlOPATIN(B, (NwLADIMIR wLADIMIROWI^s; (NlOPATIN(B, (NwLADIMIR wASILXEWI^s; (NmILOSLAWSKIJ(B, (NiGORX gRIGORXEWI^s; (N{ELQKIN(B, (NmIHAIL aLEKSEEWI^s; (NiWANOW(B, (Nw(B.(Nw(B.s ((NmOSKWA (B:s (NrUS(B. (NQZ(B.,s, 1989)
(NbIBLIOGR(B.: (NS(B. 256-257s
Keywords: (NrUSSKIJ QZYK DLQ INOSTRANCEWs